2004
DOI: 10.1111/j.1460-9592.2004.01279.x
|View full text |Cite
|
Sign up to set email alerts
|

Propofol or propofol–alfentanil anesthesia for painful procedures in the pediatric oncology ward

Abstract: If anesthesia is chosen for invasive procedures, this study suggest that propofol anesthesia in the POW is preferred by parents and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…Several TIVA regimens for pediatric oncology procedures have been reported as combinations of propofol and ketamine or opioids (fentanyl [2, 5], remifentanil [15], alfentanil [4], and morphine [16]). The Pediatric Sedation Research Consortium analyzed 49,836 propofol sedation/anesthesia encounters outside of the operating room at 37 hospitals and found that propofol alone was most commonly used (80% of cases) and that opioids were the most common addition to TIVA with propofol (~10% of cases) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several TIVA regimens for pediatric oncology procedures have been reported as combinations of propofol and ketamine or opioids (fentanyl [2, 5], remifentanil [15], alfentanil [4], and morphine [16]). The Pediatric Sedation Research Consortium analyzed 49,836 propofol sedation/anesthesia encounters outside of the operating room at 37 hospitals and found that propofol alone was most commonly used (80% of cases) and that opioids were the most common addition to TIVA with propofol (~10% of cases) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Topical 5% lidocaine and prilocaine cream (Emla) may be effective, if it is applied several hours in advance of propofol 64 ; it was ineffective when applied 1 h in advance. 65 In a placebo-controlled study in 180 adults, intravenous preinjection of diphenhydramine 20 mg or lidocaine 40 mg reduced the incidence of propofol-induced pain from 42 to 5.0% and 3.3%, respectively.…”
Section: Other Drugsmentioning
confidence: 99%
“…Therefore, this agent must be administered in a controlled setting with experienced personnel trained in advanced airway management skills with resuscitative equipment readily available. 9,21,33,51,52,55,57,58 HOW TO CHOOSE THE SEDATION CATEGORY There are several choices for sedation that can be administered in outpatient and inpatient cancer settings. Minimal sedation can be safely administered in the clinic or an inpatient unit.…”
Section: General Anesthesiamentioning
confidence: 99%